Experimental trigeminal glycerol injection in dogs: Histopathological evaluation by light and electron microscopy - (:unkn) unknown (KARGER, 2002)
We investigated the effects of percutaneous gasserian glycerol injection in dogs and reviewed the histopathological changes. Experiments were performed in 16 adult healthy mongrel dogs. In group 1 (8 dogs) normal saline and in group 2 (8 dogs) pure glycerol was injected in the right trigeminal ganglion. After these procedures, dogs in each group were sacrificed after 24 h (3 dogs), 7 days (3 dogs), 21 days (2 dogs). The trigeminal ganglion and nerve of both sides were removed by using microsurgical techniques and examined by light and electron microscopy. Group 1: in all sections, nerve cells, myelinated and nonmyelinated fibers revealed normal patterns with slight fibrosis. Group 2: in all sections, myelinated fibers showed disintegration and swelling of the myelin sheath, rupture of axon continuity, destruction of basal lamina, deformation of the myelin-axon relationship by both light microscopy and electron microscopy. The sections examined by electron microscopy also showed axonolysis in nonmyelinated fibers. The changes after 7 and 21 days were less prominent than after 24 h. In the left sides, there are no pathological changes. Glycerol has a neurolytic effect on the dog's trigeminal ganglion. These effects were not specific and selective for myelinated and nonmyelinated nerve fibers. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: dogs; glycerol; percutaneous retrogasserian glycerol rhizolysis trigeminal neuralgia; electron microscope; light microscope; GASSERIAN GANGLION; NEURALGIA; NERVE; PAIN; RHIZOTOMY; FIBERS